October sky [videorecording (DVD)] - Gyllenhaal, Jake, 1980-; Cooper, Chris, 1951-; Owen, Chris, 1980-; Dern, Laura; Hickam, Homer H., 1943- (Universal, 2005)
The true story of Homer Hickam Jr., a high school student in rural West Virginia, who seemed destined to repeat his father's harsh life in the coal mines, until he turned his attention to the skies.